Pemberdayaan Ibu untuk Perbaikan Pola Konsumsi Ikan terhadap Peningkatan Asupan Protein, Kalsium, Zink dan Z-Score Tinggi Badan Menurut Umur pada Anak Stunting - Oslida Martony; Dini Lestrina; Zul Amri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the effect of maternal empowerment on improving fish consumption patterns to increase protein intake, calcium, zinc, and Z-score height by age when stunting children. The type of this research is Quasi-Experimental with pre and post-test control group design. The results showed an increase in maternal knowledge, increased intake of protein, calcium, and zinc as well as an increase in TB scores / After the intervention in the case group, compared to the control group, there were no differences in protein, calcium intake and Z-score TB / U, an increase in maternal empowerment increased intake of children stunting and the same as intake of children not stunting. Conclusion There is a significant difference in the average value of protein intake, calcium, zinc, and Z-score before and after providing maternal empowerment interventions to improve fish consumption patterns in children aged 13-36 months. Keywords: Intake, Calcium, Maternal Empowerment, Protein, Zinc, Stunting, Z-Score TB / U